Venture Capital Sector in Pakistan: Ratio Analysis Approach for Financial Performance Assessment - Farhan, Muhammad; ., Abdul Jabbar Khan; ., Muhammad Akram (Information Management and Business Review, 2011)
The purpose of study is to rank the venture capital companies operating in Pakistan during the period of 2006-2009 on the base of their financial performance. Ratio analysis technique was used to rank the venture capital companies using profitability / efficiency ratios and total assets as proxies of financial performance. This study concludes that TRG Pakistan Limited is at first in ranking on the bases of return on assets (ROA), return on equity (ROE), and total assets, and at second on the base of earnings per share (EPS). AMZ Ventures Limited is at first on the base of earnings per share (EPS), at second in ranking on the bases of return on assets (ROA), return on equity (ROE), and total assets. TMT Ventures Limited is third on the bases of all ratios, and total assets. This is the first attempt that was made with an objective to facilitate the students, investors and management of company with useful information regarding financial performance of all venture capital companies operating in Pakistan.